Gambaran Kepadatan Tungau Debu Rumah Sebagai Pencetus Rinitis Alergi pada Anak Panti Asuhan Pekanbaru - Yolazenia Yolazenia; Harianto Harianto; Iqbal Teguh Riady (Jurnal Ilmu Kedokteran, 2019)
Allergic rhinitis should be considered as a serious condition because it can affect the quality of life of patients. In many cases, the most common allergen is house dust mites (HDM). The purpose of this study was to describe the density of house dust mites as triggers of allergic rhinitis in Pekanbaru orphanage children. This is a descriptive study with a cross sectional approach. Data obtained from interviews using the modified International Study of Asthma and Allergies of Childhood (ISAAC) questionnaire to know the allergic rhinitis status and examination of house dust samples to identify HDM in the parasitology laboratory. Sampling was carried out in 4 orphanages Pekanbaru. Allergic rhinitis symptoms were experienced by 81.2% of children in the orphanages and HDM was found with the mean density 9.11/g of dust. HDM was found in all four orphanages and was found to have a high incidence of allergic rhinitis.